2010
DOI: 10.1002/bmb.20367
|View full text |Cite
|
Sign up to set email alerts
|

Paternity testing in a PBL environment

Abstract: Problem Based Learning (PBL) makes use of real-life scenarios to stimulate students' prior knowledge and to provide a meaningful context that is also related to the student's future professional work. In this article, Paternity testing is presented using a PBL approach that involves a combination of classroom, laboratory, and out-of-class activities: in relation to a fictitious newborn found on the Campus, students design a PCR based protocol to determine their own genotype for two markers. Pooled class genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…Based on this, I can conclude that the use of PBL did not either negatively or positively affect the experimental group. This is a contrast to the results from studies by Dods (1997), Casla &Zubiaga (2010), andHeijne-Penninga et.al (2013), which found that content knowledge retention and test scores increased with the use of PBL. One possible reason for these results is that the experimental group did not connect the problem with the class material in a deep enough way as to increase their content knowledge above and beyond what they would have done using non-PBL instruction.…”
Section: Frequency Of Responses Exemplar Quotecontrasting
confidence: 97%
See 1 more Smart Citation
“…Based on this, I can conclude that the use of PBL did not either negatively or positively affect the experimental group. This is a contrast to the results from studies by Dods (1997), Casla &Zubiaga (2010), andHeijne-Penninga et.al (2013), which found that content knowledge retention and test scores increased with the use of PBL. One possible reason for these results is that the experimental group did not connect the problem with the class material in a deep enough way as to increase their content knowledge above and beyond what they would have done using non-PBL instruction.…”
Section: Frequency Of Responses Exemplar Quotecontrasting
confidence: 97%
“…After three and then seven months, the study concluded that PBL students were more likely to use science concepts and construct more accurate responses than the traditional group. In a study by Casla & Zubiaga (2010), students were monitored over four years of a PBL curriculum and consistently had higher test scores than their peers in traditional learning groups. Not only do students score higher on tests after engaging in PBL, they have more confidence in their understanding.…”
Section: Content Knowledgementioning
confidence: 99%
“…With the "Polymerase Chain Reaction" task, the participants developed solutions to a problem situation and implemented these solutions. Similarly, Casla and Zubiaga [65] reported that the problem-based activity designed on the topic of paternity testing, an application of biotechnology, strengthened teaching by using both individual and group work and combining in-class activities with out-of-class activities. Tatner and Tierney [29] reported that problem-based laboratory activities related to biotechnology issues developed problem solving and laboratory technical skills.…”
Section: Discussionmentioning
confidence: 98%
“…The PBLD format, which was first reported and further developed by Howard S. Barrows and colleagues [6,7], makes use of real-life scenarios to stimulate residents’ previous knowledge and to provide a meaningful context that is also related to the student’s future professional work, enabling active peer teaching-learning in an open communication style [8–11]. This format was selected because: 1) a simulated scenario would help engage each resident in research processes and facilitate discussion; 2) the interactive discussion among residents with varying levels of research experience would facilitate peer-to-peer learning; and 3) residents would be introduced to research resources available in their institution for each stage of research activity.…”
Section: Discussionmentioning
confidence: 99%